2014
DOI: 10.1017/s1751731114001943
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the bacterial community structure within the equine hindgut and faeces using Automated Ribosomal Intergenic Spacer Analysis (ARISA)

Abstract: The horse's hindgut bacterial ecosystem has often been studied using faecal samples. However few studies compared both bacterial ecosystems and the validity of using faecal samples may be questionable. Hence, the present study aimed to compare the structure of the equine bacterial community in the hindgut (caecum, right ventral colon) and faeces using a fingerprint technique known as Automated Ribosomal Intergenic Spacer Analysis (ARISA). Two DNA extraction methods were also assessed. Intestinal contents and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…The impact of the change of diet was marked, despite a high inter-horse variability as seen in the large mean standard errors that was found mainly in lactate concentrations in the caecum and colon. This confirmed the individual susceptibility, seen in horses fed high-starch diets as previously reported by several authors studying the equine hindgut microbial ecosystem (Julliand et al, 2001;Medina et al, 2002;Dougal et al, 2012 andSchoster et al, 2013;Sadet-Bourgeteau et al, 2014;Costa et al, 2015), and confirmed that some horses are more likely to develop digestive dysbiosis and potential intestinal diseases, such as colic. Using PCA the data showed that the two microbial ecosystems of horses clearly differed with the diet, and thus established that the hindgut microbiota was altered with the B diet.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The impact of the change of diet was marked, despite a high inter-horse variability as seen in the large mean standard errors that was found mainly in lactate concentrations in the caecum and colon. This confirmed the individual susceptibility, seen in horses fed high-starch diets as previously reported by several authors studying the equine hindgut microbial ecosystem (Julliand et al, 2001;Medina et al, 2002;Dougal et al, 2012 andSchoster et al, 2013;Sadet-Bourgeteau et al, 2014;Costa et al, 2015), and confirmed that some horses are more likely to develop digestive dysbiosis and potential intestinal diseases, such as colic. Using PCA the data showed that the two microbial ecosystems of horses clearly differed with the diet, and thus established that the hindgut microbiota was altered with the B diet.…”
Section: Discussionsupporting
confidence: 90%
“…These faecal parameters could be of particular usefulness for the diagnosis of microbial imbalances in the caecum and RV colon (the proximal hindgut). Previous studies have shown that faeces could be representative of the distal hindgut microbial composition, but not of the proximal hindgut (Da Veiga et al, 2005;Hastie et al, 2008;Dougal et al, 2012 andSchoster et al, 2013;Sadet-Bourgeteau et al, 2014;Costa et al, 2015). In this study the data demonstrated that variations in the proximal hindgut microbial ecosystem could have repercussions on the faecal one.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Given that work by Sadet-Bourgeteau et al (2010) found similarity between the right ventral colon and the caecum, it would appear that regions between the caecum and the right dorsal colon may show a gradual shift in the bacterial population. Given that work by Sadet-Bourgeteau et al (2010) found similarity between the right ventral colon and the caecum, it would appear that regions between the caecum and the right dorsal colon may show a gradual shift in the bacterial population.…”
Section: Discussionmentioning
confidence: 97%
“…Rapid fingerprinting procedures for community structure analysis (for example ARISA analysis [65] could be useful for delineating large numbers of specimen samples followed by more focused sequencing and other forms of analysis. Older methods such as DGGE and TRFLP seem to be less appropriate being costly, labour intensive, nonquantitative and given to gel-based and PCR-based biases [66] and only with limited means for sequence interrogation (e.g.…”
Section: Discussionmentioning
confidence: 99%